Thursday

April 24, 2014

April 24, 2014

Posted by **Keisha** on Wednesday, September 9, 2009 at 12:43pm.

f:x 3x+1

g:x 9-x

Determine an expression for the function gf(x)

3(9-x)+1

27-3x+1

- Math (is this correct) -
**bobpursley**, Wednesday, September 9, 2009 at 12:55pmyes, but why not combine the 27 and 1?

**Related Questions**

MATH - The function f and g are defined by : f:x --> 3x+1 g:x --> 9-x ...

add maths - Two functions f and g are defined by f:x→3x+2 and g:x→x^...

Algebra - Factor: 3x^2 - 27 3x^2-27=0 27+(3x^2-27)=0+27 3x^2=27 (3x^2)/3=27/3 x^...

algebra functions - can someone please check my answer For each problem, ...

algebra functions check my answer - For each problem, construct two composite ...

math - simplify these expressions as fractions: (26/27) + (35/4) (26/27) x (35/4...

Algebra - Does this relation define a function? y^2=3x My answer: 3x=y^2|0|3|12|...

Algebra - Does this relation define a function? y^2=3x My answer: 3x=y^2|0|3|12|...

Algebra - Two functions f and g are defined by f:x = 25 /(3x-2) g:x = x^2 Find ...

Math help please - Do the data in the table represent a linear function? If so, ...